Analysing responses to aspirin and clopidogrel by measuring platelet thrombus formation under arterial flow conditions - Hosokawa, Kazuya; Ohnishi, Tomoko; Sameshima, Hisayo; Miura, Naoki; Ito, Takashi; Koide, Takehiko; Maruyama, Ikuro (Thrombosis and Haemostasis, 2013)
High residual platelet aggregability and circulating platelet-monocyte aggregates in patients administered aspirin and clopidogrel are associated with ischaemic vascular events. To determine the relevance of these factors with residual thrombogenicity, we measured platelet thrombus formation using a microchip-based flow-chamber system in cardiac patients receiving aspirin and/or clopidogrel, and evaluated its correlation with agonist-inducible platelet aggregation and platelet-monocyte aggregates. Platelet thrombus formation was analysed by measuring flow pressure changes due to the occlusion of micro-capillaries and was quantified by calculating AUC10 (area under the flow pressure curve). The growth and stability of platelet thrombi that formed inside microchips at shear rates of 1000, 1500, and 2000 s-1 were markedly reduced in patients receiving aspirin and/or thienopyridine compared to healthy controls (n=33). AUC10 values of aspirin therapy patients (n=20) were significantly lower and higher than those of healthy controls and dual antiplatelet therapy patients (n=19), respectively, and showed relatively good correlations with collagen-induced platelet aggregation and platelet-monocyte aggregates at 1000 and 1500 s-1 (rs>0.59, p<0.01). In contrast, AUC10 in dual antiplatelet therapy patients was significantly correlated with ADP-induced platelet aggregation at all examined shear rates (rs>0.59, p<0.01), but did not correlate with collagen-induced aggregation. Aspirin monotherapy patients with high residual platelet thrombogenicity also exhibited significant elevations in both collagen-induced platelet aggregation and platelet-monocyte aggregates. Our results, although preliminary, suggest that residual platelet thrombogenicity in aspirin-treated patients is associated with either collagen-induced platelet aggregation or circulating platelet-monocyte aggregates, but it is predominantly dependent on ADP-induced platelet aggregation in patients receiving dual antiplatelet therapy.
Keywords: Antiplatelet therapy; aspirin; clopidogrel; platelet thrombus; blood flow